Avaliação da bioatividade e estudo da composição química do óleo essencial das folhas de Zanthoxylum tingoassuiba A.ST. HIL - Nogueira, Jeane Andréia Pedrosa (2014)
Zanthoxylum tingoassuiba is a species from the Rutaceae family, commonly known as guando-do-mato , mamica - de - porca e limãozinho . This work describes the analysis of the essential chemical composition of its leaves oil having identified the sylvestrene as a major component, through CGMS analysis. It is the first time that constituents muurola - trans - 4,5 - diene and isodaucene are identified in an essential oil from this species. It was observed, for insecticidal activity of the essential oil against the insect Rhodnius prolixus, one of the vectors of Chagas disease, a high mortality rate, malformation and paralysis in fifth instar nymphs. It was also evaluated against phytophagous Oncopeltus fasciatus and Dysdercus peruvianus, that are insects pests of crops. In Dysdercus peruvianus the process of metamorphosis and intermolt period were affected, some of the treated insects presented malformation and a high mortality rate. In Oncopeltus fasciatus, the treatment with pure oil and dilutions of 250.00mg/mL and 500.00mg/mL presented 100% mortality rate. In the acaricidal activity evaluation, changes occurred in oviposition, decreased hatchability of eggs and 100 % mortality at a concentration of 5 %. It also shows that the effectiveness of the essential oil is dose dependent. These results suggests that the essential oil from leaves Z. tingoassuiba can be used as actives in bioacaricidal formulations in the future, being part of the cattle tick therapeutics, a bioagent that causes huge damage to livestock. This work reports the insecticidal and acaricidal activities for Zanthoxylum tingoassuiba, showing that the species has a biotechnological potential for further studies